2017
DOI: 10.1007/s11187-017-9967-2
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and start-up rates in different geographies: Belgium, the Netherlands, and Sweden

Abstract: This study addresses the mediating role of settlement patterns in the relationship between urbanization and start-up activity. Places do not operate in a vacuum and to understand the effect of Bown^density on start-up patterns, we need to account for the urban spillovers or borrowed size that they may experience from other places nearby. The results can explain the empirical ambiguity in the relationship between urbanization and start-up patterns: the relationship between urbanization and start-up rates become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Pensioners contribute to the local development and economic entrepreneurship of the suburban area [65]. Hans and Koster [66] point out in some countries the positive participation of 65+ seniors in setting up start-ups, which may be a form of partial retirement. Sometimes, however, migration from urban to peri-urban regions due to second homes or retirement can directly or indirectly affect the socio-spatial conflicts that make it difficult for new residents to take root.…”
Section: Rural Areas In Poland and Economic Consequences Of Migrationmentioning
confidence: 99%
“…Pensioners contribute to the local development and economic entrepreneurship of the suburban area [65]. Hans and Koster [66] point out in some countries the positive participation of 65+ seniors in setting up start-ups, which may be a form of partial retirement. Sometimes, however, migration from urban to peri-urban regions due to second homes or retirement can directly or indirectly affect the socio-spatial conflicts that make it difficult for new residents to take root.…”
Section: Rural Areas In Poland and Economic Consequences Of Migrationmentioning
confidence: 99%
“…In regional analyses, urbanization economies are used as a variable to explain that in denser or larger cities, businesses obtain profits related to the concentration of businesses, consumers, universities and government offices. A study that reviewed the economies of three countries found both a negative impact of urbanization on the creation of new businesses in the Netherlands and Belgium and a zero impact in the case of Sweden (Hans and Koster, 2018). The authors argued that urbanization should be analyzed along with other economic characteristics.…”
Section: Introductionmentioning
confidence: 99%